Perceived size of a line depending on its projection place on the retina - Dzekevičiūtė, A.; Daugirdienė, A.; Švegžda, A.; Stanikūnas, R.; Vaitkevičius, H. (Psichologija, 2011)
It is known that objects located in the centre of the visual field are perceived as larger than the objects located in the periphery (Пиаже, 1978). The image of an object differs from its perception object. The perceived size of an object depends on the size of its image in the visual cortex. This stems from the so-called cortical magnification factor. It is assumed that the same quantity of receptors sends information to the same area of the cortex. But photoreceptors are different – rods and the cones. It is not clear whether the different types of receptors make a different influence on the above-mentioned distortion of mapping. Also, the image of the object on the retina is perceived differently, depending on its location on the retina. Our goal was to explore how this subjective expansion changes while moving away from the centre of the retina, because there are no data on this, phenomenon.Method. Thirty normal or corrected to normal vision adults participated in the study. Five different length lines (5, 7, 10, 13, 15 degrees) were represented on the computer’s monitor one line at a time. Participants had monoculary bisected lines into two subjectively equal parts fixating sight on a cross located at the given end of the line.Results. The ratio ρ (length of the line near the cross / length of the other part) was calculated. This ratio as a function of the length of the whole line was not monotonic: when the line was short, ρ decreased, but then it began to increase. Three groups of results were formed considering the ratio of the line length (where the function had the extremum point). The largest group (66.67%) had the extremum point when the line length was 7 deg. The second group (23.33%) had the extremum point when the line length was 13 deg. The last group (10%) had not clear extremum point and was excluded from the calculation. Changes of the ρ value cannot be explained by the perceptual instability of the length of the line (Brown, 1953). There could be a correlation between the value of ρ and the density of all receptors in the retina where the line was projected.Conclusions. Humans make a bias while monocular by bisecting a line: the part near the point of fixation is perceived as bigger than the other part. The function of the line size ratio changes not monotonically – it has an extremum point. Most often, the extremum point is observed when the line size is 7 deg. This point is near the point where the density of rods exceeds that of cones. Other subjects show the extremum point when the line size is 13 deg., but the reasons for such a point shift remain unclear. Some subjects have no extremum point.
Keywords: size perception; cortical magnification factor; density of photoreceptors